Pengaruh Pendidikan Kewirausahaan dan Latar Belakang Keluarga Terhadap Minat Berwirausaha Mahasiswa Di Tengah Situasi Pandemi (Sukabumi) - Anugerah Nur Raya (Economic Education and Entrepreneurship Journal, 2021)
This study aims to determine the effect of entrepreneurship education and family background on student interest in entrepreneurship in the city of Sukabumi during this corona pandemic era. The method used is a survey method. This survey method is carried out by distributing questionnaires to 100 sample people. As well as for testing the quality of the instrument, using validity and reliability testing techniques. And for testing the hypothesis using multiple regression analysis, partial t-test, and simultaneous f-test. The result is known that the variables of Entrepreneurship Education and Family Background affect Entrepreneurial Interest. And there are variables of Entrepreneurship Education and Family Background simultaneously influencing Entrepreneurial InterestKeywords : Entrepreneurship Education, Family Background, Interest in Entrepreneurship, Covid_19